PENGARUH SISTEM DAN PROSEDUR PEMUNGUTAN PAJAK KENDARAAN BERMOTOR TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (STUDI PADA BADAN PENDAPATAN DAERAH UPT PENDAPATAN WILAYAH MAKASSAR 1) (Indonesian Journal Of Law Studies, 2023)
This study aims to determine and analyze the effect of the System and Procedures for collecting Motor Vehicle Tax on increasing Regional Original Income Data collection uses Primary data obtained by conducting direct research to the Office of the Regional Revenue Agency, UPT Makassar Regional Revenue 1 and using purposive sampling. The population in this study was 145,107 taxpayers who owned motorized vehicles in the Makassar City area at the Regional Revenue Agency, UPT Makassar Regional Revenue 1. The samples were taken using the slovin formula so that a sample of 99 respondents was obtained. The results of the research variables have been tested by assumptions. classic form of normality test, heteroscedasticity test. Methods of data analysis using simple regression techniques, and hypothesis testing after the data was collected, the data were analyzed using the SPSS (Statistical Product and Service Solution) version 26 program.The results showed that the system and procedure variables for collecting motorized vehicle tax (X) had a positive and significant effect on the Regional Original Income variable (Y). namely 2,389 1,660. This shows the influence of several aspects, namely taxpayers more easily and quickly accessing motorized vehicle tax payments, fulfilling, and understanding their rights and obligations.